2013
DOI: 10.1177/1756285613499424
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of laquinimod in multiple sclerosis: current status

Abstract: Laquinimod is a novel immunomodulatory agent, in development as a potential disease-modifying treatment for multiple sclerosis (MS). Structurally related to linomide, its pharmacological predecessor, laquinimod combines anti-inflammatory and possibly clinically relevant neuroprotective effects with the convenience of oral administration. In this review we aim to highlight the immunomodulatory and neuroprotective effects of laquinimod, and to describe its effects in animal models of MS. Furthermore, we focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In contrast, compounds targeting the aryl hydrocarbon receptor (AhR) which is also a ligand-activated nuclear transcription factor and a member of the basic helix-loop-helix (bHLH) family has not been approved for any pharmacologic applications. There are only a few AhR ligands including aminoflavone and laquinomod that have been in clinical trials for treatment of breast cancer and multiple sclerosis, respectively (Haggiag et al 2013; Loaiza-Perez et al 2004). …”
Section: Cancer Chemotherapies and A Role For The Ahrmentioning
confidence: 99%
“…In contrast, compounds targeting the aryl hydrocarbon receptor (AhR) which is also a ligand-activated nuclear transcription factor and a member of the basic helix-loop-helix (bHLH) family has not been approved for any pharmacologic applications. There are only a few AhR ligands including aminoflavone and laquinomod that have been in clinical trials for treatment of breast cancer and multiple sclerosis, respectively (Haggiag et al 2013; Loaiza-Perez et al 2004). …”
Section: Cancer Chemotherapies and A Role For The Ahrmentioning
confidence: 99%
“…Tolerogenic DCs induce T cell apoptosis, anergy and regulatory T cells (Tregs; Li and Shi, 2015 ). Not surprisingly then, it has also been found that LAQ augmented the Treg cell response leading to further anti-inflammatory effects (Haggiag et al, 2013 ). It is important to note that ex vivo studies did not replicate the increase in CD86 (Stasiolek et al, 2015 ).…”
Section: Laquinimodmentioning
confidence: 97%
“…NF-κB is required for maturation of DCs, which in turn induces T cell differentiation (Jolivel et al, 2013 ). Thus, blockage of NF-κB by LAQ, creates an immature DC phenotype with reduced ability to induce CD4 + T cell proliferation, pro-inflammatory cytokine secretion, chemokine production and consequent migration of monocytes as well as a decrease in DC number (Haggiag et al, 2013 ). However, unlike the effects of DMF, where CD86 and CD80 were down-regulated, LAQ upregulates CD86 while not modulating CD80 (Jolivel et al, 2013 ).…”
Section: Laquinimodmentioning
confidence: 99%
“…(5-chloro-N-ethyl-4-hydroxy-1-methyl-2-oxo-N-phenyl-1,2-dihydroquinoline-3-carboxamide [LAQ]), also known as ABR-215062, is structurally related to linomide (roquinimex), which demonstrated efficacy in murine acute experimental autoimmune encephalomyelitis (EAE) and later in MS [103]. However, due to severe immune-mediated side effects (serositis, pericarditis, myocardial infarction) observed during two Phase III trials [104,105], the clinical development of linomide was halted.…”
Section: Laquinimodmentioning
confidence: 99%